Intelligent transportation systems - Figueiredo, Lino (2019)
This paper presents a review of the state of the art on Intelligent Transportation Systems and discuss the problem of modelling and simulation. ITS involves a large number of research ares and, therefore, this paper focus on those we believe to be the most relevant.